Analysis of Mathematical Concepts in the Traditional Palak Babi Game of Bengkulu Province - Harahap, Mardhatillah Hafidzah; Risnanosanti, Risnanosanti; Kashardi, Kashardi (Unnes Journal of Mathematics Education, 2024)
Analysis of Mathematical Concepts in the Traditional Palak Babi Game of Bengkulu Province. Culture is the identity of a nation that is formed from values, beliefs, customs, and norms that are held firmly and passed down from generation to generation. The culture of a region is reflected in various aspects of people's lives, one of which is through traditional games in Bengkulu Province. The traditional game is the traditional Palak Babi game, which effectively contributes to building mathematical concepts. Mathematical concepts appear in society and culture. Ethnomathematics is the study of mathematical concepts in traditional games as a culture. The purpose of this research was to analyze the mathematical concepts that were naturally involved in the traditional Palak Babi game. The method used in this research was the descriptive qualitative method. The concepts include measurement, comparison, addition, multiplication, and angles. Thus, the traditional Palak Babi game as part of culture contains valuable ethnomathematical values. Therefore, it can provide new insights into developing more contextualized mathematics learning strategies and expand understanding of mathematics.